Resin Composition for Anti-reflective Film, Anti-reflective Film and Solid State Imaging Device

KR1020260133558APending Publication Date: 2026-09-04DONGWOO FINE CHEM CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
KR1020250026909
Authority / Receiving Office
KR · KR
Patent Type
Applications
Current Assignee / Owner
Filing Date
2025-02-28
Publication Date
2026-09-04

Smart Images

  • Figure PAT00001
    Figure PAT00001
  • Figure PAT00002
    Figure PAT00002
  • Figure PAT00003
    Figure PAT00003
Patent Text Reader

Abstract

The present invention provides a resin composition for an anti-reflective film comprising hollow aluminosilicate particles, a binder resin, and a solvent, wherein the hollow aluminosilicate particles have a Si / Al molar ratio of 7 to 15 and their surface is modified with a silane compound of a specific structure or a non-reactive resin, and the solvent comprises an alcohol compound in a specific content; an anti-reflective film formed therefrom; and a solid-state imaging device comprising said anti-reflective film. The resin composition for an anti-reflective film according to the present invention exhibits a low refractive index, suppresses crack formation during film formation, has excellent flatness of the film, prevents particle aggregation and foreign matter generation, prevents moisture adsorption under high temperature and high humidity conditions, prevents moisture penetration by a developer and a stripper, and also has excellent stability over time.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to a resin composition for an anti-reflective film, an anti-reflective film, and a solid-state imaging device, and more specifically, to a resin composition for an anti-reflective film, an anti-reflective film, and a solid-state imaging device that exhibits a low refractive index, suppresses crack formation during film formation, has excellent flatness of the film, prevents particle aggregation and foreign matter generation, prevents moisture adsorption under high temperature and high humidity conditions, prevents moisture penetration by a developer and a stripper, and also has excellent stability over time. Background Technology

[0002] A solid-state imaging device is a device that converts an image captured through light energy into electrical information. Micro-lenses for light focusing are formed on the photoelectric converter, and an anti-reflective film is formed on the surface. This anti-reflective film serves to prevent noise such as flare or ghosting.

[0003] Anti-reflective films applied to solid-state imaging devices require fine and precise processing and moldability. For this reason, conventional vapor deposition methods suitable for micro-processing, such as vacuum deposition or sputtering, have been adopted.

[0004] However, vapor phase methods such as vacuum deposition or sputtering have the problem of high manufacturing costs due to the high cost of equipment.

[0005] Accordingly, a coating method is being proposed in which a composition capable of forming an anti-reflective film is applied and cured on a substrate to replace the vapor phase method.

[0006] For example, Korean Patent Publication No. 10-2010-0123610 discloses a method for forming an anti-reflective film by applying a coating solution containing hollow silica particles and a binder resin as low-refractive-index particles.

[0007] However, conventional anti-reflective film compositions using hollow silica particles had problems such as a tendency for cracking to occur during film formation, poor film flatness, moisture adsorption under high temperature and humidity conditions, and moisture permeability caused by developers and strippers.

[0008] Furthermore, untreated hollow silica particles have hydrophilic surface characteristics that allow them to absorb moisture from the air, leading to particle aggregation and reduced fluidity. Additionally, their poor miscibility with polymeric materials or organic solvents in the composition results in the formation of foreign substances, which can cause quality degradation.

[0009] In addition, if the compatibility between hollow silica particles and the solvent is poor, their dispersibility becomes poor, which presents a problem in that it is difficult to ensure stability over time.

[0010] Therefore, there is a need to develop a resin composition for anti-reflective films that exhibits a low refractive index, suppresses crack formation during film formation, provides excellent film flatness, prevents particle aggregation and foreign matter generation, prevents moisture adsorption under high temperature and high humidity conditions, blocks moisture penetration by developers and strippers, and also has excellent stability over time. Prior art literature

[0011] Republic of Korea Published Patent No. 10-2010-0123610 The problem to be solved

[0012] One objective of the present invention is to provide a resin composition for an anti-reflective film that exhibits a low refractive index, suppresses crack formation during film formation, has excellent film flatness, prevents particle aggregation and foreign matter generation, prevents moisture adsorption under high temperature and high humidity conditions, prevents moisture penetration by developers and strippers, and also has excellent stability over time.

[0013] Another objective of the present invention is to provide an anti-reflection film formed using the resin composition for the anti-reflection film.

[0014] Another objective of the present invention is to provide a solid-state imaging element having the anti-reflective film. means of solving the problem

[0015] On the one hand, the present invention comprises hollow aluminosilicate particles, a binder resin, and a solvent, and

[0016] The above hollow aluminosilicate particles have a Si / Al molar ratio of 7 to 15, and their surfaces are modified with a compound represented by the following chemical formula 1 or a non-reactive resin, and

[0017] The above solvent provides a resin composition for an anti-reflective film that contains an alcohol compound in an amount of 5 to 50 weight% based on 100 weight% of the total solvent.

[0018] [Chemical Formula 1]

[0019]

[0020] In the above formula,

[0021] R 1 C1-C 20 It is an alkyl group of, and

[0022] R 2 to R 4 Each is independently a C1-C4 alkoxy group.

[0024] In one embodiment of the present invention, the average particle size of the hollow aluminosilicate particles may be 30 to 150 nm.

[0025] In one embodiment of the present invention, the non-reactive resin may include a repeating unit represented by the following chemical formula 2.

[0026] [Chemical Formula 2]

[0027]

[0028] In the above formula,

[0029] R 5 is a hydrogen atom or a methyl group, and

[0030] L 1is non-existent or C1-C 10 The alkylene group or C1-C 10 It is an oxyalkylene group, and

[0031] R 6 It is a hydroxyl group, a C1-C4 alkoxy group, or a halogen, and

[0032] R 7 Silver is a hydrogen atom or C1-C 20 It is an alkyl group of, and

[0033] n is an integer from 1 to 3.

[0035] In one embodiment of the present invention, the alcohol compound is C1-C 10 It may be a monoalcohol compound.

[0036] In one embodiment of the present invention, the alcohol compound may be one or more selected from the group consisting of methanol, ethanol, isopropyl alcohol, butanol, pentanol, hexanol, and 3-methoxy-1-butanol.

[0038] A resin composition for an anti-reflective film according to one embodiment of the present invention may further include amorphous silica particles.

[0039] A resin composition for an anti-reflective film according to one embodiment of the present invention can satisfy the following mathematical formula 1.

[0040] [Mathematical Formula 1]

[0041] 1 ≤ a / b ≤ 15

[0042] In the above formula,

[0043] a is the average particle size of hollow aluminosilicate particles, and b is the average particle size of amorphous silica particles.

[0045] In one embodiment of the present invention, the cured film formed from the resin composition for the anti-reflective film may have a refractive index of 1.20 to 1.35 at 550 nm.

[0047] On the other hand, the present invention provides an anti-reflective film formed using the resin composition for the anti-reflective film.

[0048] On the other hand, the present invention provides a solid-state imaging element having the anti-reflective film. Effects of the invention

[0049] The resin composition for an anti-reflective film according to the present invention exhibits a low refractive index, suppresses crack formation during film formation, provides excellent flatness of the film, prevents particle aggregation and foreign matter generation, prevents moisture adsorption under high temperature and high humidity conditions, prevents moisture penetration by developer and stripper solutions, and also exhibits excellent stability over time. Therefore, the resin composition for an anti-reflective film according to the present invention can be advantageously applied to an anti-reflective film of a solid-state imaging device. Specific details for implementing the invention

[0050] The present invention will be described in more detail below.

[0052] One embodiment of the present invention comprises hollow aluminosilicate particles (A), a binder resin (C), and a solvent (D), and

[0053] The above hollow aluminosilicate particles have a Si / Al molar ratio of 7 to 15, and their surfaces are modified with a compound represented by the following chemical formula 1 or a non-reactive resin, and

[0054] The above-mentioned solvent relates to a resin composition for an anti-reflective film that contains an alcohol compound in an amount of 5 to 50 weight percent based on 100 weight percent of the total solvent.

[0055] [Chemical Formula 1]

[0056]

[0057] In the above formula,

[0058] R 1 C1-C 20 It is an alkyl group of, and

[0059] R 2 to R 4 Each is independently a C1-C4 alkoxy group.

[0061] The above Si / Al molar ratio refers to the molar ratio of silicon (Si) elements in the hollow aluminosilicate particles and aluminum (Al) elements used for modification.

[0062] The above Si / Al molar ratio is 7 to 15, preferably 7 to 12, as described above. If the above Si / Al molar ratio is less than 7, the aluminum content increases, and a complete hollow shape may not be formed due to micropores occurring on the shell surface. Consequently, the strength of the hollow particles decreases, making it impossible to manufacture high-density hollow particles. Additionally, undissolved aluminum may remain in the shell, which may cause an increase in the refractive index and lead to aggregation of particles. If the ratio exceeds 15, when forming micropores in the shell, not only the aluminum on the shell surface but also the core particles are not completely removed, which causes an increase in the refractive index and makes it difficult to maintain the hollow shape during a hydrothermal reaction.

[0064] In one embodiment of the present invention, the cured film formed from the resin composition for the anti-reflective film may have a refractive index of 1.20 to 1.35 at 550 nm.

[0065] By controlling the refractive index at 550 nm of the cured film formed from the above anti-reflective resin composition to the above range, it is positioned on top of a high-refractive index layer having a refractive index of 1.60 or higher, thereby eliminating noise such as flare or ghost, and thus improving the light-gathering efficiency of the solid-state imaging element.

[0067] Hollow aluminosilicate particles (A)

[0068] In one embodiment of the present invention, the hollow aluminosilicate particles (A) serve to improve anti-reflection properties by lowering the refractive index while maintaining the strength of the coating film.

[0069] The above hollow aluminosilicate particles (A) are silica particles modified with Al, and the Si / Al molar ratio is 7 to 15, preferably 7 to 12.

[0070] As the above hollow aluminosilicate particles (A) are modified with Al, they have low aggregation and excellent dispersibility, and can have high density through hydrothermal reaction.

[0071] The above-described hollow aluminosilicate particles can be obtained by preparing core-shell particles in which an aluminosilicate shell is formed by reacting a silane compound and an aluminum (Al) precursor with a template core consisting of micelles or reverse micelles of an organic polymer, and then reacting the core-shell particles with a basic or acidic aqueous solution to form micropores in the shell while simultaneously removing the core. If necessary, the density of the hollow aluminosilicate particles can be further increased by hydrothermal reaction.

[0072] The organic polymer forming the micelle or reverse micelle above is an amphoteric polymer having both hydrophobic and hydrophilic properties, and may be, for example, polyoxyethylene tallowamine, polyoxyethylene olillamine, polyoxyethylene stearylamine, polyoxyethylene laurylamine, polyoxyethylene sorbitan ester, polyoxyethylene octyl ether, etc. These organic polymers may be used alone or in combination of two or more types.

[0073] The above organic polymer forms micelles or reverse micelles in a solvent. At this time, the type of solvent is not particularly limited and can be selected and used according to the characteristics of the organic polymer. Specifically, the solvent may be an alcohol, a glycol ester, a ketone, or a mixture thereof. The alcohol may be methanol, ethanol, isopropanol, etc.; the glycol ester may be methyl cellosolve, ethyl cellosolve, etc.; and the ketone may be methyl ethyl ketone, methyl isobutyl ketone, etc.

[0074] The above silane compound can be easily combined with an organic polymer that forms a template core. This combination can be carried out by the Stober method (Werner, 1968), and when preparing a shell by the sol-gel process using the Stober method, a stable shell can be prepared through hydrolysis and condensation synthesis by an acidic or basic solution contained in the solvent.

[0075] The above silane compounds may include alkoxysilanes, chlorosilanes, bromosilanes, etc., without limitation. For example, the above silane compounds may include tetramethoxysilane, tetraethoxysilane, tetraisopropoxysilane, phenyltrimethoxysilane, diphenyldimethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, γ-glycidoxytripropyltrimethoxysilane, γ-(meth)acryloxypropyltrimethoxysilane, γ-aminopropyltrimethoxysilane, γ-mercaptopropyltrimethoxysilane, trimethylchlorosilane, trimethylbromosilane, etc. These silane compounds may be used alone or in combination of two or more.

[0076] The type of the above aluminum precursor is not particularly limited, and, for example, an organic salt or alkoxide of aluminum may be used.

[0077] The above silane compound and aluminum precursor combine with the core material to form an aluminosilicate shell, thereby producing core-shell particles. The produced core-shell particles can be reacted with a basic aqueous solution or an acidic aqueous solution to form micropores in the shell, and since the micropores formed in this way facilitate the entry and exit of dissolved organic polymers, the organic polymers inside the shell can be easily removed through a simple washing step.

[0078] Sodium hydroxide, ammonium hydroxide, potassium hydroxide, phosphate hydroxide, or a mixture thereof may be used as the basic aqueous solution, and hydrochloric acid, nitric acid, sulfuric acid, acetic acid, or a mixture thereof may be used as the acidic aqueous solution.

[0079] As the above-mentioned washing solvent, distilled water, alcohol, glycol, glycol ester, or a mixture thereof may be used. As the alcohol, methanol, ethanol, isopropanol, etc. may be used; as the glycol, ethylene glycol, propylene glycol, etc. may be used; and as the glycol ester, ethyl cellosolve, methyl cellosolve, etc. may be used.

[0080] The above hydrothermal reaction can be carried out at a temperature of 160 to 250°C.

[0082] In one embodiment of the present invention, the average particle size of the hollow aluminosilicate particles may be 30 to 150 nm, preferably 40 to 120 nm, and more preferably 50 to 90 nm. If the average particle size of the hollow aluminosilicate particles is within the above range, it may be easy to control them to satisfy Equation 1 described below, and the refractive index of the cured film may be controlled more effectively. If the average particle size of the hollow aluminosilicate particles is less than 30 nm, the volume of air within the hollow aluminosilicate particles decreases, so the refractive index cannot be lowered, and it may be difficult to maintain the hollow shape because it breaks easily due to the thickness of the thin shell, and if it exceeds 150 nm, the flatness of the coating film is reduced, and a difference in refractive index may occur even within the coating film.

[0084] The above hollow aluminosilicate particles have their surfaces modified with a compound represented by the following chemical formula 1 or a non-reactive resin.

[0085] [Chemical Formula 1]

[0086]

[0087] In the above formula,

[0088] R 1 C1-C 20 It is an alkyl group of, and

[0089] R 2 to R 4Each is independently a C1-C4 alkoxy group.

[0091] C1-C used in this specification 20 The alkyl group refers to a straight-chain or branched hydrocarbon composed of 1 to 20 carbon atoms, and includes, but is not limited to, methyl, ethyl, n-propyl, i-propyl, n-butyl, i-butyl, t-butyl, pentyl, hexyl, 2-ethylhexyl, heptyl, 2-ethylheptyl, octyl, nonyl, decyl, undecyl, dodecyl, tridecyl, tetradecyl, pentadecyl, hexadecyl, heptadecyl, stearyl, nonadecyl, eicosanyl, etc.

[0092] As used in this specification, C1-C4 alkoxy groups refer to straight-chain or branched alkoxy groups composed of 1 to 4 carbon atoms, and include but are not limited to methoxy, ethoxy, n-propanoxy, etc.

[0094] The compound represented by the above chemical formula 1 serves to prevent the aggregation of silicate particles due to the non-reactive alkyl group.

[0095] If the compound used for the above surface modification is a reactive compound, aggregation of hollow aluminosilicate particles occurs, impairing dispersion stability. During film formation, the aggregated particles manifest as foreign matter, and not only does the flatness of the film become poor, but the high temperature and high humidity permeability and the permeability caused by the developer and stripper may also become poor.

[0096] In one embodiment of the present invention, R 1 is preferably C1-C 15 The alkyl group of, more preferably C1-C 10 The alkyl group of, more preferably C2-C 10 It can be an alkyl group of. R 1 If the chain length is long, steric hindrance can prevent the aggregation of hollow aluminosilicate particles and improve dispersibility. However, R 1If the chain length becomes too long, compatibility with polymeric materials or organic solvents in the composition decreases, leading to particle precipitation or gelation. This not only results in poor storage stability but can also lead to poor moisture permeability due to high temperature and humidity, as well as moisture permeability caused by developers and strippers. 1 If the chain length is within the above-mentioned desirable range, the dispersibility is excellent, particle aggregation is suppressed during film formation, and the flatness of the film is excellent.

[0098] The above non-reactive resin may include repeating units represented by the following chemical formula 2.

[0099] [Chemical Formula 2]

[0100]

[0101] In the above formula,

[0102] R 5 is a hydrogen atom or a methyl group, and

[0103] L 1 is non-existent or C1-C 10 The alkylene group or C1-C 10 It is an oxyalkylene group, and

[0104] R 6 It is a hydroxyl group, a C1-C4 alkoxy group, or a halogen, and

[0105] R 7 Silver is a hydrogen atom or C1-C 20 It is an alkyl group of, and

[0106] n is an integer from 1 to 3.

[0108] C1-C used in this specification 10 The alkylene group refers to a straight-chain or branched divalent hydrocarbon composed of 1 to 10 carbon atoms, and includes, but is not limited to, methylene, ethylene, n-propylene, isopropylene, n-butylene, isobutylene, n-pentylene, n-hexylene, n-heptylene, n-octylene, n-nonylene, etc.

[0109] C1-C used in this specification 10The oxyalkylene group refers to a functional group in which one or more of the chain carbons in a straight-chain or branched divalent hydrocarbon consisting of 1 to 10 carbon atoms are substituted with oxygen, and includes, but is not limited to, oxymethylene, oxyethylene, oxypropylene, oxybutylene, oxypentylene, oxyhexylene, etc.

[0111] The above non-reactive resin may further include repeating units represented by the following chemical formula 3.

[0112] [Chemical Formula 3]

[0113]

[0114] In the above formula,

[0115] R 8 It is a hydrogen atom or a methyl group, and

[0116] L 2 is not present or C1-C 18 It is an alkylene group.

[0118] C1-C used in this specification 18 The alkylene group refers to a straight-chain or branched divalent hydrocarbon composed of 1 to 18 carbon atoms, and includes, but is not limited to, methylene, ethylene, n-propylene, isopropylene, n-butylene, isobutylene, n-pentylene, n-hexylene, n-heptylene, n-octylene, n-nonylene, etc.

[0120] Preferably, L 2 It may not exist or may be a C1-C6 alkylene group.

[0122] In one embodiment of the present invention, the repeating unit represented by Formula 2 may be included in an amount of 30 to 99 mole%, preferably 50 to 95 mole%, and more preferably 60 to 90 mole%, based on 100 mole% of the total repeating units constituting the non-reactive resin. When the repeating unit represented by Formula 2 is included within the above mole% range, it has high reactivity with the silanol groups (Si-OH) on the silica surface, thereby increasing the efficiency of surface modification.

[0123] In one embodiment of the present invention, the repeating unit represented by Formula 3 may be included in an amount of 1 to 70 mol%, preferably 5 to 50 mol%, and more preferably 10 to 40 mol%, based on 100 mol% of the total repeating units constituting the non-reactive resin. When the repeating unit represented by Formula 3 is included within the mol% range, it is desirable to assist in the hydrolysis of the alkoxy groups, for example, by adjusting the pH.

[0125] The above non-reactive resin may include additional repeating units in addition to the repeating units represented by the above chemical formulas 2 to 3.

[0126] The above non-reactive resin may be a block copolymer in which the repeating units represented by the above chemical formulas 2 to 3 are each repeated in a constant manner, or a random copolymer in which they are repeated randomly.

[0127] The method for manufacturing the above-mentioned non-reactive resin is not particularly limited, and methods known in the relevant technical field may be used.

[0128] The above non-reactive resin may have a polystyrene equivalent weight-average molecular weight (hereinafter simply referred to as "weight-average molecular weight") measured by gel permeation chromatography (GPC; using tetrahydrofuran as the elution solvent) of 3,000 to 8,000. It is desirable that the weight-average molecular weight of the above non-reactive resin is within the above range, as this results in excellent hydrophobicity of the modified surface.

[0130] Surface modification of the above hollow aluminosilicate particles can be performed by hydrolyzing a compound represented by Chemical Formula 1 or a non-reactive resin to form a silanol (-Si-OH) group and then reacting it with the hollow aluminosilicate particles.

[0132] The above hollow aluminosilicate particles may be included in an amount of 10 to 99 weight%, preferably 40 to 95 weight%, based on 100 weight% of the total solid content of the resin composition for the anti-reflective film. When amorphous silica particles described later are further included, the above hollow aluminosilicate particles may be included in an amount of 20 to 80 weight%, preferably 35 to 75 weight%, based on 100 weight% of the total solid content of the resin composition for the anti-reflective film. If the above hollow aluminosilicate particles are included in an amount less than the above content range, they cannot exhibit a low refractive index effect and thus cannot perform the function of an anti-reflective film, and if they are included in an amount exceeding the above content range, the formation of the coating film is not easy.

[0134] Binder resin (C)

[0135] In one embodiment of the present invention, the binder resin (C) has reactivity due to the action of heat and performs the function of a binding resin.

[0136] In addition, the above binder resin (C) has excellent moisture resistance and chemical resistance under high temperature and high humidity environments, and can play a role in preventing the decrease in anti-reflection efficiency caused by an increase in the refractive index.

[0137] In one embodiment of the present invention, the binder resin may be used as long as it is a thermosetting resin, without any particular limitations.

[0138] For example, siloxane resin can be used as the binder resin mentioned above.

[0139] Commercially available products can be used as the above siloxane resin.

[0140] In addition, a polysiloxane compound may be used as the binder resin.

[0141] The above polysiloxane compound may include a hydrolysis condensate of a silane compound represented by the following chemical formula 4.

[0142] [Chemical Formula 4]

[0143] R 9 m Si(OR 10 ) 4-m

[0144] In the above formula,

[0145] R 9 is C1-C 20 It is an alkyl group, vinyl group, aryl group, or aralkyl group, and

[0146] R 10 is a C1-C4 alkyl group, and

[0147] m is an integer from 0 to 3.

[0149] As used herein, aryl groups include aromatic groups, heteroaromatic groups, and their partially reduced derivatives. The aromatic group is a simple or fused ring type with 5 to 15 members, and the heteroaromatic group refers to an aromatic group containing one or more oxygen, sulfur, or nitrogen. Representative examples of aryl groups include, but are not limited to, phenyl, naphthyl, pyridinyl, pyrimidinyl, pyrrolyl, furanyl, thiophenyl, indolyl, quinolinyl, imidazolyl, oxazolyl, thiazolyl, tetrahydronaphthyl, and pyridinyl.

[0150] As used in this specification, the aralkyl group refers to a complex group formed by substituting an aryl group (aromatic hydrocarbon group) on a carbon of an alkyl group, and includes, but is not limited to, examples such as benzyl and phenethyl.

[0151] As used in this specification, C1-C4 alkyl groups refer to straight-chain or branched monovalent hydrocarbons having 1 to 4 carbon atoms, and include, but are not limited to, methyl, ethyl, n-propyl, i-propyl, n-butyl, i-butyl, t-butyl, etc.

[0153] In one embodiment of the present invention, in terms of improving crosslinkability and thereby increasing the degree of curing and improving the reliability of the coating film, the polysiloxane compound may include a hydrolysis condensate of a mixture of silane compounds represented by the following chemical formulas 4-1 to 4-4.

[0154] [Chemical Formula 4-1]

[0155] Si(OR 10 )4

[0156] [Chemical Formula 4-2]

[0157] R 9 Si(OR 10 )3

[0158] [Chemical Formula 4-3]

[0159] R 9 2Si(OR 10 )2

[0160] [Chemical Formula 4-4]

[0161] R 9 3Si(OR 10 )

[0162] In the above formula,

[0163] R 9 is C1-C 20 It is an alkyl group, vinyl group, aryl group, or aralkyl group, and

[0164] R 10 is a C1-C4 alkyl group.

[0166] Examples of silane compounds represented by the above chemical formula 4-1 include tetramethoxysilane, tetraethoxysilane, tetra-n-propoxysilane, tetra-i-propoxysilane, tetra-n-butoxysilane, etc.

[0167] Examples of silane compounds represented by the above chemical formula 4-2 include methyltrimethoxysilane, methyltriethoxysilane, methyltripropoxysilane, methyltributoxysilane, ethyltrimethoxysilane, ethyltriethoxysilane, phenyltrimethoxysilane, phenyltriethoxysilane, benzyltrimethoxysilane, benzyltriethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, etc.

[0168] Examples of silane compounds represented by the above chemical formula 4-3 include dimethyldimethoxysilane, dimethyldiethoxysilane, diethyldimethoxysilane, diethyldiethoxysilane, phenylmethyldimethoxysilane, phenylmethyldiethoxysilane, diphenyldimethoxysilane, diphenyldiethoxysilane, benzylmethyldimethoxysilane, benzylmethyldiethoxysilane, etc.

[0169] Examples of silane compounds represented by the above chemical formula 4-4 include trimethylmethoxysilane, triethylmethoxysilane, triethylmethoxysilane, triethylethoxysilane, triphenylmethoxysilane, triphenylethoxysilane, benzyldimethylmethoxysilane, benzyldimethylethoxysilane, etc.

[0171] The mixing ratio of the silane compounds represented by the above chemical formulas 4-1 to 4-4 may be 1 : 1.5 to 2.5 : 2.5 to 3.5 : 3.5 to 4.5 on a molar basis in terms of controlling the degree of crosslinking of the polysiloxane.

[0173] The above polysiloxane compound can be prepared by the hydrolysis sol-gel reaction of a silane compound represented by the above chemical formula 4.

[0174] Specifically, the alkoxy group of the starting material, a silane compound represented by Chemical Formula 4, is hydrolyzed with water to form a hydroxyl group, and a polysiloxane is formed by forming a siloxane bond through a condensation reaction with the alkoxy group or hydroxyl group of another silane compound represented by Chemical Formula 4.

[0175] Preferably, a catalyst may be added to promote the above hydrolysis sol-gel reaction. Suitable catalysts include acid catalysts such as acetic acid, phosphoric acid, sulfuric acid, hydrochloric acid, nitric acid, chlorosulfonic acid, para-toluene, trichloroacetic acid, polyphosphoric acid, phyllophosphoric acid, iodic acid, tartaric acid, and perchloric acid; base catalysts such as ammonia, sodium hydroxide, n-butylamine, di-n-butylamine, tri-n-butylamine, imidazole, ammonium perchlorate, potassium hydroxide, and barium hydroxide; and ion exchange resins such as Amberite IPA-400(Cl). The amount of catalyst used is not particularly limited and may be added in an amount of 0.0001 to 10 parts by weight per 100 parts by weight of the silane compound.

[0176] The above hydrosol-gel reaction may be carried out by stirring at room temperature for 6 to 144 hours, and may also be carried out at 60 to 80°C for 4 to 36 hours to accelerate the reaction rate and ensure the progress of a complete condensation reaction.

[0178] In addition, as the above-mentioned binder resin, a binder resin having thermosetting functional groups such as hydroxyl groups, epoxy groups, and oxetane groups within the molecule may be used.

[0179] For example, the binder resin having the thermosetting functional group may include one or more repeating units represented by the following chemical formulas 5 to 9.

[0180] [Chemical Formula 5]

[0181]

[0182] [Chemical Formula 6]

[0183]

[0184] [Chemical Formula 7]

[0185]

[0186] [Chemical Formula 8]

[0187]

[0188] [Chemical Formula 9]

[0189]

[0190] In the above formula,

[0191] R 11 to R 16 Each is independently a hydrogen atom or a methyl group, and

[0192] L 3 to L 6 Each does not exist independently or C1-C 10 The alkylene group or C1-C 10 It is an oxyalkylene group, and

[0193] R 17 It is a residue containing a hydrogen atom or a carboxylic acid derived by an acid anhydride.

[0195] The acid anhydrides used herein include succinic anhydride, methylsuccinic anhydride, (2-dodecen-1-yl)succinic anhydride, phenylsuccinic anhydride, phthalic anhydride, maleic anhydride, citraconic anhydride, glutaric anhydride, 3,3-dimethylglutaric anhydride, itaconic anhydride, 3,4,5,6-tetrahydrophthalic anhydride, trimellitic anhydride, The acid anhydride includes, but is not limited to, hexahydrophthalic anhydride and carbic anhydride. In terms of ease of reaction, it is preferable to use maleic anhydride, phthalic anhydride, trimellitic anhydride, succinic anhydride, hexahydrophthalic anhydride and / or carbic anhydride as the acid anhydride, and trimellitic anhydride, succinic anhydride and / or hexahydrophthalic anhydride are particularly preferred.

[0197] The binder resin having the above-mentioned thermosetting functional group may further include other repeating units in addition to the above-mentioned repeating unit.

[0198] For example, the binder resin having the thermosetting functional group may further include repeating units derived from an ethylenically unsaturated monomer having a carboxyl group.

[0199] Specific examples of the ethylenically unsaturated monomer having the above-mentioned carboxyl group include monocarboxylic acids such as acrylic acid, methacrylic acid, and crotonic acid; dicarboxylic acids such as fumaric acid, mesaconic acid, and itaconic acid; anhydrides of these dicarboxylic acids; and mono(meth)acrylates of polymers having carboxyl and hydroxyl groups at both ends, such as ω-carboxypolycaprolactone mono(meth)acrylate. Among these, acrylic acid and methacrylic acid are preferred.

[0200] In addition, the binder resin having the above-mentioned thermosetting functional group may further include repeating units derived from monomers having other unsaturated double bonds.

[0201] Specific examples of monomers having the above-mentioned unsaturated double bond include:

[0202] Hydroxyalkyl (meth)acrylate compounds such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, and 2-hydroxy-3-phenoxypropyl (meth)acrylate;

[0203] Aromatic vinyl compounds such as styrene, vinyltoluene, α-methylstyrene, p-chlorostyrene, o-methoxystyrene, m-methoxystyrene, p-methoxystyrene, o-vinylbenzylmethyl ether, m-vinylbenzylmethyl ether, p-vinylbenzylmethyl ether, o-vinylbenzylglycidyl ether, m-vinylbenzylglycidyl ether, p-vinylbenzylglycidyl ether;

[0204] N-substituted maleimide compounds such as N-cyclohexylmaleimide, N-benzylmaleimide, N-phenylmaleimide, No-hydroxyphenylmaleimide, Nm-hydroxyphenylmaleimide, Np-hydroxyphenylmaleimide, No-methylphenylmaleimide, Nm-methylphenylmaleimide, Np-methylphenylmaleimide, No-methoxyphenylmaleimide, Nm-methoxyphenylmaleimide, Np-methoxyphenylmaleimide, etc.;

[0205] Alkyl (meth)acrylate compounds such as methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, i-propyl (meth)acrylate, n-butyl (meth)acrylate, i-butyl (meth)acrylate, sec-butyl (meth)acrylate, t-butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate;

[0206] cyclophenyl(meth)acrylate compounds such as cyclopentyl(meth)acrylate, cyclohexyl(meth)acrylate, 2-methylcyclohexyl(meth)acrylate, 2-dicyclofentanyloxyethyl(meth)acrylate, isobornyl(meth)acrylate, etc.;

[0207] Aryl (meth)acrylates such as phenyl (meth)acrylate and benzyl (meth)acrylate;

[0208] Unsaturated oxetane compounds such as 3-(methacryloyloxymethyl)oxetane, 3-(methacryloyloxymethyl)-3-ethyloxetane, 3-(methacryloyloxymethyl)-2-trifluoromethyloxetane, 3-(methacryloyloxymethyl)-2-phenyloxetane, 2-(methacryloyloxymethyl)oxetane, 2-(methacryloyloxymethyl)-4-trifluoromethyloxetane;

[0209] Vinyl carboxylate ester compounds such as vinyl acetate, vinyl propionate, etc.;

[0210] Examples include vinyl cyanide compounds such as (meth)acrylonitrile and α-chloroacrylonitrile. These can be used individually or in combination of two or more.

[0212] The method for manufacturing the binder resin having the above-mentioned thermosetting functional group is not particularly limited, and methods known in the relevant technical field may be used.

[0214] The above-mentioned binder resin may be included in an amount of 1 to 90 weight%, preferably 5 to 60 weight%, based on 100 weight% of the total solid content of the resin composition for the anti-reflective film. When the amorphous silica particles described below are further included, the above-mentioned binder resin may be included in an amount of 1 to 50 weight%, preferably 5 to 30 weight%, based on 100 weight% of the total solid content of the resin composition for the anti-reflective film. When the above-mentioned binder resin satisfies the above range, it maintains stability even at high temperatures and has high resistance to many chemicals, thereby improving chemical resistance, corrosion resistance, etc. If the above-mentioned binder resin is included in an amount less than the above-mentioned content range, the adhesion to the substrate and chemical resistance may be poor due to insufficient curing, and if it is included in an amount exceeding the above-mentioned content range, the relative particle content may decrease, and the refractive index may increase.

[0216] Solvent (D)

[0217] The above solvent (D) includes an alcohol compound to ensure excellent compatibility with hollow aluminosilicate particles.

[0218] The above alcohol compound may be a monoalcohol compound.

[0219] As used in this specification, monoalcohol compounds refer to alcohol compounds having a saturated hydrocarbon group having 1 to 10 carbon atoms and one hydroxyl group.

[0220] The above saturated hydrocarbon group is a C1-C group in which one or more of the chain carbons are substituted with oxygen or are not substituted. 10 It can be an alkyl group.

[0221] The above alcohol compound has excellent compatibility with hollow aluminosilicate particles, C1-C 10 The monoalcohol compound may be, preferably, a C1-C6 monoalcohol compound.

[0222] Specifically, the alcohol compound may be one or more selected from the group consisting of methanol, ethanol, isopropyl alcohol, butanol, pentanol, hexanol, and 3-methoxy-1-butanol.

[0223] In particular, 1-pentanol can be used as the alcohol compound due to its excellent compatibility with hollow aluminosilicate particles.

[0224] The above alcohol compound is included in an amount of 5 to 50 weight percent based on 100 weight percent of the total solvent.

[0225] When an alcohol compound is included as a solvent within the above content range, excellent compatibility with hollow aluminosilicate particles is secured, and the dispersibility of the hollow aluminosilicate particles is improved, resulting in excellent storage stability.

[0226] If the alcohol compound is included in an amount of less than 5% by weight relative to 100% by weight of the total solvent, it may reduce the dispersibility of hollow aluminosilicate particles, resulting in poor storage stability, and if it is included in an amount of more than 50% by weight, it may result in poor coating performance of the substrate and cause haze in the coating film due to insufficient compatibility with the binder resin in the composition.

[0228] The above solvent (D) includes other solvents in addition to the alcohol compound described above.

[0229] The above other solvents are not particularly limited and various organic solvents used in the relevant technical field may be used.

[0230] Specific examples of the other solvents mentioned above include ethylene glycol monoalkyl ethers such as ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monopropyl ether, and ethylene glycol monobutyl ether; diethylene glycol dialkyl ethers such as diethylene glycol dimethyl ether, diethylene glycol diethyl ether, diethylene glycol ethylmethyl ether, diethylene glycol dipropyl ether, and diethylene glycol dibutyl ether; ethylene glycol alkyl ether acetates such as methyl cellosolve acetate, ethyl cellosolve acetate, ethylene glycol monobutyl ether acetate, and ethylene glycol monoethyl ether acetate; and alkylene glycol alkyl ether acetates such as propylene glycol monomethyl ether acetate, propylene glycol monoethyl ether acetate, propylene glycol monopropyl ether acetate, methoxybutyl acetate, and methoxypentyl acetate. Propylene glycol monoalkyl ethers such as propylene glycol monomethyl ether, propylene glycol monoethyl ether, propylene glycol monopropyl ether, and propylene glycol monobutyl ether; propylene glycol dialkyl ethers such as propylene glycol dimethyl ether, propylene glycol diethyl ether, propylene glycol ethyl methyl ether, propylene glycol dipropyl ether, and propylene glycol ethyl propyl ether; propylene glycol alkyl ether propionates such as propylene glycol methyl ether propionate, propylene glycol ethyl ether propionate, propylene glycol propyl ether propionate, and propylene glycol butyl ether propionate; butanediol monoalkyl ether acetates such as methoxybutyl acetate, ethoxybutyl acetate, propoxybutyl acetate, and butoxybutyl acetate; Butanediol monoalkyl ether propionates such as methoxybutylpropionate, ethoxybutylpropionate, propoxybutylpropionate, and butoxybutylpropionate; dipropylene glycol dialkyl ethers such as dipropylene glycol dimethyl ether, dipropylene glycol diethyl ether, and dipropylene glycol methyl ethyl ether; aromatic hydrocarbons such as benzene, toluene, xylene, and mesitylene; ketones such as methyl ethyl ketone, acetone, methyl amyl ketone, methyl isobutyl ketone, and cyclohexanone;Methyl acetate, ethyl acetate, propyl acetate, butyl acetate, 2-ethyl hydroxypropionate, 2-methyl-2-methylpropionate, 2-ethyl-2-hydroxypropionate, methyl hydroxyacetate, ethyl hydroxyacetate, butyl hydroxyacetate, methyl lactate, ethyl lactate, propyl lactate, butyl lactic acid, 3-methyl hydroxypropionate, 3-ethyl hydroxypropionate, 3-propyl hydroxypropionate, 3-butyl hydroxypropionate, 2-methyl-3-methylbutanoate, methyl methoxyacetate, ethyl methoxyacetate, propyl methoxyacetate, butyl methoxyacetate, methyl ethoxyacetate, ethyl ethoxyacetate, propyl ethoxyacetate, Butyl ethoxyacetate, methyl propoxyacetate, ethyl propoxyacetate, propyl propoxyacetate, butyl propoxyacetate, methyl butoxyacetate, ethyl butoxyacetate, propyl butoxyacetate, butyl butoxyacetate, 2-methyl methoxypropionate, 2-ethyl methoxypropionate, 2-propyl methoxypropionate, 2-butyl methoxypropionate, 2-methyl ethoxypropionate, 2-ethyl ethoxypropionate, 2-propyl ethoxypropionate, 2-butyl ethoxypropionate, 2-methyl butoxypropionate, 2-ethyl butoxypropionate, 2-propyl ethoxypropionate, 2-butyl methoxypropionate, 3-methyl methoxypropionate, 3-ethyl methoxypropionate, Examples include esters such as 3-propyl methoxypropionate, 3-butyl methoxypropionate, 3-methyl ethoxypropionate, 3-ethyl ethoxypropionate, 3-propyl ethoxypropionate, 3-butyl ethoxypropionate, 3-methyl propoxypropionate, 3-ethyl propoxypropionate, 3-propyl propoxypropionate, 3-butyl propoxypropionate, 3-methyl butoxypropionate, 3-ethyl butoxypropionate, 3-propyl butoxypropionate, 3-butoxypropionate, 3-butoxypropionate, and 3-butoxypropionate; cyclic ethers such as tetrahydrofuran and pyran; and cyclic esters such as γ-butyrolactone. The solvents exemplified herein may each be used individually or in a mixture of two or more types.

[0231] Considering the coating properties and drying properties, the above solvent may preferably be diethylene glycol dialkyl ethers, alkylene glycol alkyl ether acetates, ketones, butanediol alkyl ether acetates, ethyl 3-ethoxypropionate, methyl 3-methoxypropionate, etc., and more preferably diethylene glycol ethyl methyl ether, propylene glycol monomethyl ether acetate, propylene glycol monoethyl ether acetate, cyclohexanone, methoxybutyl acetate, ethyl 3-ethoxypropionate, methyl 3-methoxypropionate, etc. may be used.

[0233] The above solvent may be included in an amount of 90 to 97 weight percent based on 100 weight percent of the total resin composition for the anti-reflective film. It is desirable for the content of the above solvent to be within the above range, as this results in good applicability when applied using an application device such as a spin coater, slit-and-spin coater, slit coater (sometimes called a die coater or curtain flow coater), or inkjet.

[0235] A resin composition for an anti-reflective film according to one embodiment of the present invention may further include amorphous silica particles (B).

[0237] Amorphous silica particles (B)

[0238] In one embodiment of the present invention, the amorphous silica particles (B) serve to suppress crack formation while maintaining film strength and improve the flatness of the film.

[0239] The above amorphous silica particles (B) are silica particles that do not have a hollow space within their structure and lack regularity in particle shape.

[0240] The above amorphous silica particles (B) can be obtained from the market and used.

[0241] For example, the above amorphous silica particles (B) include MT-10, DM-10, DM-30, DM-20S, DM-30S, KS-20SC, HG-09, HM-20L, HM-30S, ZD-30ST, PM-09, PM-20, X-20, X-30 (manufactured by Tokuyama Corporation), but are not limited thereto.

[0242] In one embodiment of the present invention, the average particle size of the amorphous silica particles may be 7 to 25 nm, preferably 7 to 22 nm. If the average particle size of the amorphous silica particles is within the above range, it may be easy to control to satisfy Equation 1 described below, and the refractive index of the cured film may be controlled more effectively. If the average particle size of the amorphous silica particles is less than 7 nm, gelation of the particles during storage may not be suppressed, and if it exceeds 25 nm, the refractive index increases, the surface roughness of the coating film increases, and haze may occur.

[0244] The above amorphous silica particles may be included in an amount of 70% by weight or less, for example, 10 to 70% by weight, preferably 20 to 50% by weight, based on 100% by weight of the total solid content of the resin composition for the anti-reflective film. When the above amorphous silica particles are included within the above content range, sufficient filling occurs between the hollow aluminosilicate particles within the coating film, thereby lowering the surface roughness of the coating film. If the above amorphous silica particles are included in an amount exceeding 70% by weight, the content of the hollow aluminosilicate particles is relatively reduced, making it difficult to lower the refractive index.

[0246] A resin composition for an anti-reflective film according to one embodiment of the present invention can satisfy the following mathematical formula 1.

[0247] [Mathematical Formula 1]

[0248] 1 ≤ a / b ≤ 15

[0249] In the above formula,

[0250] a is the average particle size of hollow aluminosilicate particles, and b is the average particle size of amorphous silica particles.

[0252] The above a / b value is the ratio of the average particle size of hollow aluminosilicate particles to amorphous silica particles. If the above a / b value is less than 1, the refractive index increases due to the large particle size of the amorphous silica particles, and the flatness of the coating film may decrease because the amorphous silica particles do not sufficiently fill the spaces between the hollow aluminosilicate particles. If it is greater than 15, the flatness of the coating film may decrease due to the large particle size of the hollow aluminosilicate particles.

[0254] A resin composition for an anti-reflective film according to one embodiment of the present invention may further include a leveling agent.

[0255] As the leveling agent mentioned above, commercially available surfactants may be used, such as silicone-based, fluorine-based, ester-based, cationic, anionic, nonionic, amphoteric surfactants, etc., and each of these may be used individually or in combination of two or more types.

[0256] Examples of the above silicone-based surfactants include commercially available products such as DC3PA, DC7PA, SH11PA, SH21PA, SH8400 from Dow Corning Toray Silicon, and TSF-4440, TSF-4300, TSF-4445, TSF-4446, TSF-4460, TSF-4452 from GE Toshiba Silicon. Examples of the above fluorine-based surfactants include commercially available products such as MegaPac F-470, F-471, F-475, F-482, F-489, F-554 from Dainippon Ink & Chemical Co., Ltd.

[0257] The leveling agent may be included in an amount of 0.0001 to 0.01 weight% based on 100 weight% of the total resin composition for the anti-reflective film. It is desirable that the content of the leveling agent be within the above range, as this results in excellent film-forming properties of the resin composition for the anti-reflective film and good flatness of the film formed therefrom.

[0259] A resin composition for an anti-reflective film according to one embodiment of the present invention may additionally include, in addition to the above-mentioned components, additives such as a curing agent, a slip improver, an adhesion promoter, an antioxidant, a UV absorber, an anti-aggregation agent, a radical generator, and a photocatalyst, as needed.

[0260] The above-mentioned curing agent is used to increase deep curing and mechanical strength, and specific examples of the curing agent include epoxy compounds, polyfunctional isocyanate compounds, melamine compounds, oxetane compounds, etc.

[0261] Specific examples of epoxy compounds in the above curing agent include bisphenol A-based epoxy resin, hydrogenated bisphenol A-based epoxy resin, bisphenol F-based epoxy resin, hydrogenated bisphenol F-based epoxy resin, novolak-type epoxy resin, other aromatic epoxy resins, alicyclic epoxy resins, glycidyl ester-based resins, glycidylamine-based resins, or brominated derivatives of such epoxy resins, aliphatic, alicyclic, or aromatic epoxy compounds other than epoxy resins and their brominated derivatives, butadiene (co)polymer epoxides, isoprene (co)polymer epoxides, glycidyl (meth)acrylate (co)polymers, triglycidyl isocyanurate, etc.

[0262] Specific examples of oxetane compounds in the above curing agent include carbonate bis-oxetane, xylene bis-oxetane, adipate bis-oxetane, terephthalate bis-oxetane, cyclohexanedicarboxylic acid bis-oxetane, etc.

[0263] The above curing agent may be used in combination with a curing aid compound capable of ring-opening polymerization of the epoxy groups of the epoxy compound or the oxetane backbone of the oxetane compound. Examples of the above curing aid compound include polycarboxylic acids, polycarboxylic anhydrides, acid generators, etc.

[0264] The above-mentioned carboxylic acid anhydrides may be commercially available as epoxy resin curing agents. Examples of the above-mentioned epoxy resin curing agents include the product name (Adeka Hadona EH-700) (manufactured by Adeka Industry Co., Ltd.), the product name (Ricasitdo HH) (manufactured by Shin Nippon Iwa Co., Ltd.), and the product name (MH-700) (manufactured by Shin Nippon Iwa Co., Ltd.). The curing agents exemplified above may be used alone or in a mixture of two or more types.

[0265] Examples of the above-mentioned slip-improving agents include commercially available products such as BYK-333 (BYK Corporation).

[0266] As for the above adhesion promoter, a silane-based compound is preferred, and specifically, examples include vinyltrimethoxysilane, vinyltriethoxysilane, vinyltris(2-methoxyethoxy)silane, N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane, N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 3-chloropropylmethyldimethoxysilane, 3-chloropropyltrimethoxysilane, 3-methacryloyloxypropyltrimethoxysilane, 3-mercaptopropyltrimethoxysilane, 3-isocyanatepropyltriethoxysilane, etc.

[0267] Specifically, the above antioxidants include 2-tert-butyl-6-(3-tert-butyl-2-hydroxy-5-methylbenzyl)-4-methylphenylacrylate, 2-[1-(2-hydroxy-3,5-di-tert-pentylphenyl)ethyl]-4,6-di-tert-pentylphenylacrylate, 6-[3-(3-tert-butyl-4-hydroxy-5-methylphenyl)propoxy]-2,4,8,10-tetra-tert-butyldibenz[d,f][1,3,2]dioxafosperpine, 3,9-bis[2-{3-(3-tert-butyl-4-hydroxy-5-methylphenyl)propionyloxy}-1,1-dimethylethyl]-2,4,8,10-tetraoxaspiro[5.5]undecane, 2,2'-Methylenebis(6-tert-butyl-4-methylphenol), 4,4'-Butylidenebis(6-tert-butyl-3-methylphenol), 4,4'-Thiobis(2-tert-butyl-5-methylphenol), 2,2'-Thiobis(6-tert-butyl-4-methylphenol), Dilauryl 3,3'-Thiodipropionate, Dimyristyl 3,3'-Thiodipropionate, Distearyl 3,3'-Thiodipropionate, Pentaerythrityltetrakis(3-Laurylthiopropionate), 1,3,5-Tris(3,5-di-tert-butyl-4-hydroxybenzyl)-1,3,5-Triazine-2,4,6(1H,3H,5H)-Trione, Examples include 3,3',3'',5,5',5''-hexa-tert-butyl-a,a',a''-(mesitylene-2,4,6-triyl)tri-p-cresol, pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], 2,6-di-tert-butyl-4-methylphenol, etc.

[0268] Specifically, examples of the above-mentioned ultraviolet absorbers include 2-(3-tert-butyl-2-hydroxy-5-methylphenyl)-5-chlorobenzotriazole, alkoxybenzophenone, etc.

[0269] Specifically, the above anti-aggregation agents include sodium polyacrylate.

[0270] Examples of the above radical generators include commercially available products such as OXE 01 (BASF).

[0271] Examples of the above-mentioned photocatalytic agents include commercially available products such as Irgacure 290 (BASF).

[0273] One embodiment of the present invention relates to an anti-reflective film formed using the resin composition for an anti-reflective film described above.

[0274] According to the present invention, the anti-reflective film can be manufactured by applying the resin composition for the anti-reflective film described above onto a substrate and then applying heat.

[0275] A preferred example of the manufacturing process is to apply a resin composition for an anti-reflective film onto a substrate and then heat-dry it to remove volatile components such as solvents, thereby obtaining a smooth coating film.

[0276] As for the application method, it may be carried out by, for example, spin coating, flexible coating, roll coating, slit and spin coating, or slit coating.

[0277] After coating, heat drying (pre-baking) or vacuum drying is performed, and then heating is done to volatilize volatile components such as solvents. Here, the heating temperature is typically 70 to 200°C, preferably 80 to 130°C.

[0278] Subsequently, exposure and development processes can be performed as needed.

[0279] Finally, a heating process (post-baking) is performed again to form a cured network. Here, the heating temperature is typically around 70 to 230°C. As a heating method, a hot plate, a clean oven, or an infrared heater may be used. However, the present invention does not limit the heating method.

[0280] A cured film can be formed on a substrate by using the resin composition for an anti-reflective film of the present invention and going through each of the above processes.

[0281] The hardened film obtained in this way can be usefully used as an anti-reflective film for solid-state imaging devices.

[0283] Accordingly, one embodiment of the present invention relates to a solid-state imaging element having the anti-reflection film described above.

[0284] The above-mentioned solid-state imaging element may include, for example, a CCD (Charged Coupled Device) or a CMOS (Complementary Metal Oxide Semiconductor, CMOS) image sensor.

[0285] The above-described solid-state imaging element includes a support comprising a semiconductor element or a photoelectric conversion element and a microlens, and the anti-reflective film may be formed on the microlens.

[0287] The present invention will be explained more specifically below through examples, comparative examples, and experimental examples. These examples, comparative examples, and experimental examples are intended solely to illustrate the present invention, and it is obvious to those skilled in the art that the scope of the present invention is not limited thereto.

[0289] Synthesis Example 1: Preparation of non-reactive resin

[0290] A flask equipped with a stirrer, thermometer, reflux condenser, dropping lot, and nitrogen inlet tube was prepared. Subsequently, a polymerizable mixture containing 91.2 g (0.35 mol, 70 mol%) of 3-diethoxymethylsilylpropyl methacrylate and 12.9 g (0.15 mol, 30 mol%) of methacrylic acid was prepared.

[0291] Afterwards, 4g of t-butylperoxy-2-ethylhexanoate and 40g of propylene glycol monomethyl ether acetate (PGMEA) were added to the polymerizable mixture and stirred to prepare a monomer solution, and a mixed solution of 6g of n-dodecanethiol and 24g of PGMEA was prepared as a chain transfer agent.

[0292] Afterward, 395g of PGMEA was introduced into the flask, the atmosphere inside the flask was changed from air to nitrogen, and the temperature of the flask was raised to 70℃ while stirring. The monomer solution and the chain transfer agent were each added dropwise into the flask through a dropping lot over a period of 2 hours while maintaining the temperature at 70℃.

[0293] After 1 hour, the temperature was raised to 75°C and maintained for 12 hours, after which, bubbling of an oxygen / nitrogen 5 / 95 (v / v) mixed gas was initiated through the gas inlet tube. Subsequently, 0.4 g of 2,2'-methylenebis(4-methyl-6-t-butylphenol) and 0.8 g of triethylamine were added to the flask and reacted at 70°C for 8 hours to obtain non-reactive resin 1.

[0294] The solid dispersion value of the resin synthesized in this way was 92.3 mgKOH / g, and the weight-average molecular weight Mw measured by GPC was approximately 4,500.

[0296] Synthesis Example 2: Preparation of Non-Reactive Resin

[0297] Non-reactive resin 2 was obtained by the same method as in Synthesis Example 4, except that 3-methacryloxypropyl triethoxysilane was used instead of 3-diethoxymethylsilylpropyl methacrylate.

[0298] The solid dispersion value of the resin synthesized in this way was 97.3 mgKOH / g, and the weight-average molecular weight Mw measured by GPC was approximately 5,500.

[0300] Preparation Example 1-1: Preparation of hollow aluminosilicate particles (A-1)

[0301] A core template for a hollow shape was prepared by adding 0.172 g of polyacrylic acid, 0.086 g of polystyrene sulfonic acid, and 3 ml of ammonium hydroxide to a 1 L three-necked round-bottom flask, followed by the addition of 60 ml of ethanol. While stirring the solution, 8 ml of 3% aluminum isopropoxide and 60 ml of ethanol containing tetraethoxysilane were added using a syringe pump to obtain spherical particles containing the core. These particles were reacted with 5% sodium hydroxide, then washed and dried with distilled water and alcohol to produce aluminosilicate particles having a hollow shape. 20 g of the prepared particles and 80 g of distilled water were added and ultrasonically dispersed using an ultrasonic disperser for 1 hour to prepare an aqueous dispersion of aluminosilicate stably dispersed in water. This dispersion was placed in a 1L hydrothermal reactor and reacted at 180°C for 10 hours, after which it was precipitated and dried to produce hollow aluminosilicate particles with increased shell density. The solvent was substituted with propylene glycol monomethyl ether acetate to prepare an aluminosilicate propylene glycol monomethyl ether acetate dispersion with a solid content of 10 wt%. The average particle size was 78 nm, and the Si / Al molar ratio was 12.

[0303] Preparation Example 1-2: Preparation of hollow aluminosilicate particles (A-2)

[0304] A dispersion of hollow aluminosilicate particles was obtained in the same manner as in Preparation Example 1-1, except that 10 ml of 3% aluminum isopropoxide was used. The average particle size was 40 nm, and the Si / Al molar ratio was 10.

[0306] Preparation Example 1-3: Preparation of hollow aluminosilicate particles (A-3)

[0307] A dispersion of hollow aluminosilicate particles was obtained in the same manner as in Preparation Example 1-1, except that 12 ml of 3% aluminum isopropoxide was used. The average particle size was 150 nm, and the Si / Al molar ratio was 8.

[0309] Preparation Example 1-4: Preparation of hollow aluminosilicate particles (A-4)

[0310] A dispersion of hollow aluminosilicate particles was obtained in the same manner as in Preparation Example 1-1, except that 6 ml of 3% aluminum isopropoxide was used. The average particle size was 74 nm, and the Si / Al molar ratio was 16.

[0312] Preparation Example 1-5: Preparation of hollow aluminosilicate particles (A-5)

[0313] A dispersion of hollow aluminosilicate particles was obtained in the same manner as in Preparation Example 1-1, except that 20 ml of 3% aluminum isopropoxide was used. The average particle size was 74 nm, and the Si / Al molar ratio was 5.

[0315] Preparation Example 2-1: Preparation of surface-modified hollow aluminosilicate particles (F-1)

[0316] Surface-modified hollow aluminosilicate particles were prepared by applying the method described in the paper Korean Chem. Eng. Res., Vol. 49, No. 2, April, 2011, pp. 181-186.

[0317] Specifically, the hollow aluminosilicate particles (A-1) prepared in Preparation Example 1-1 above were dried in a dry oven at 120°C for at least 3 hours, then cooled to room temperature in a desiccator to remove adsorbed moisture before use. For the solvent, 300 ml of ethanol and deionized water were prepared at a ratio of 80:20 (v / v%) at room temperature and pressure, the pH was adjusted to 3 to 5 using acetic acid, and the mixture was stirred at 300 rpm for approximately 30 minutes using a magnetic stirrer. R was added to the stirred solvent 1 is a methyl group, and R 2 to R 425.0 g of compound (E-1), represented by Chemical Formula 1 and containing a methoxy group, was added and stirred at 300 rpm for 1 hour to hydrolyze the alkoxy groups bonded to the Si terminals. After the hydrolysis reaction was completed, 5.0 g of the water-removed hollow aluminosilicate particles (A-1) from Preparation Example 1-1 were placed in a round flask, and a surface modification reaction was carried out at 300 rpm for 2 hours. The reaction solution was centrifuged using a centrifuge (SUPRA 21K, Hanil Science) at 3,000 rpm for 30 minutes, and the supernatant was discarded. The particles were washed several times with an ethanol / deionized water (80:20 v / v%) solution and pure ethanol, and after centrifugation, dried in a vacuum oven at 40°C for 24 hours to obtain surface-modified hollow aluminosilicate particles (F-1). .

[0319] Preparation Example 2-2: Preparation of surface-modified hollow aluminosilicate particles (F-2)

[0320] The above R 1 is a methyl group, and R 2 to R 4 R instead of the compound (E-1) represented by Chemical Formula 1, which is a methoxy group 1 is an ethyl group, and R 2 to R 4 Surface-modified hollow aluminosilicate particles (F-2) were prepared in the same manner as in Preparation Example 2-1, except that a compound (E-2) represented by Chemical Formula 1, which is a methoxy group, was used.

[0322] Preparation Example 2-3: Preparation of surface-modified hollow aluminosilicate particles (F-3)

[0323] The above R 1 is a methyl group, and R 2 to R 4 R instead of the compound (E-1) represented by Chemical Formula 1, which is a methoxy group 1 is a pentadecyl group, and R 2 to R 4Surface-modified hollow aluminosilicate particles (F-3) were prepared in the same manner as in Preparation Example 2-1, except that a compound (E-3) represented by Chemical Formula 1, which is an ethoxy group, was used.

[0325] Preparation Example 2-4: Preparation of surface-modified hollow aluminosilicate particles (F-4)

[0326] The above R 1 is a methyl group, and R 2 to R 4 R instead of the compound (E-1) represented by Chemical Formula 1, which is a methoxy group 1 is a pentacosanyl group, and R 2 to R 4 Surface-modified hollow aluminosilicate particles (F-4) were prepared in the same manner as in Preparation Example 2-1, except that a compound (E-4) represented by Chemical Formula 1, which is an ethoxy group, was used.

[0328] Preparation Example 2-5: Preparation of surface-modified hollow aluminosilicate particles (F-5)

[0329] The above R 1 is a methyl group, and R 2 to R 4 Surface-modified hollow aluminosilicate particles (F-5) were prepared in the same manner as in Preparation Example 2-1, except that 3-aminopropyl triethoxysilane (KBM-903) (E-5) was used instead of the compound represented by Chemical Formula 1 (E-1), which is a methoxy group.

[0331] Preparation Example 2-6: Preparation of surface-modified hollow aluminosilicate particles (F-6)

[0332] The above R 1 is a methyl group, and R 2 to R 4 Surface-modified hollow aluminosilicate particles (F-6) were prepared in the same manner as in Preparation Example 2-1, except that 3-methacryloxypropyl trimethoxysilane (KBM-503) (E-6) was used instead of the compound represented by Chemical Formula 1 (E-1), which is a methoxy group.

[0334] Preparation Example 2-7: Preparation of surface-modified hollow aluminosilicate particles (F-7)

[0335] The above R 1 is a methyl group, and R 2 to R 4 Surface-modified hollow aluminosilicate particles (F-7) were prepared in the same manner as in Preparation Example 2-1, except that 3-mercaptopropylmethyldimethoxysilane (KBM-802) (E-7) was used instead of the compound represented by Chemical Formula 1 (E-1), which is a methoxy group.

[0337] Preparation Example 2-8: Preparation of surface-modified hollow aluminosilicate particles (F-8)

[0338] Surface-modified hollow aluminosilicate particles (F-8) were prepared in the same manner as in Preparation Example 2-1, except that hollow aluminosilicate particles (A-2) of Preparation Example 1-2 were used instead of hollow aluminosilicate particles (A-1) of Preparation Example 1-1.

[0340] Preparation Example 2-9: Preparation of surface-modified hollow aluminosilicate particles (F-9)

[0341] Surface-modified hollow aluminosilicate particles (F-9) were prepared in the same manner as in Preparation Example 2-1, except that hollow aluminosilicate particles (A-3) of Preparation Example 1-3 were used instead of hollow aluminosilicate particles (A-1) of Preparation Example 1-1.

[0343] Preparation Example 2-10: Preparation of surface-modified hollow aluminosilicate particles (F-10)

[0344] Using the hollow aluminosilicate particles (A-4) of Preparation Example 1-4 instead of the hollow aluminosilicate particles (A-1) of Preparation Example 1-1, and the R 1 is a methyl group, and R 2 to R 4 R instead of the compound (E-1) represented by Chemical Formula 1, which is a methoxy group 1 is an ethyl group, and R 2 to R 4Surface-modified hollow aluminosilicate particles (F-10) were prepared in the same manner as in Preparation Example 2-1, except that a compound (E-2) represented by Chemical Formula 1, which is a methoxy group, was used.

[0346] Preparation Example 2-11: Preparation of surface-modified hollow aluminosilicate particles (F-11)

[0347] Using the hollow aluminosilicate particles (A-5) of Preparation Example 1-5 instead of the hollow aluminosilicate particles (A-1) of Preparation Example 1-1, and the R 1 is a methyl group, and R 2 to R 4 R instead of the compound (E-1) represented by Chemical Formula 1, which is a methoxy group 1 is an ethyl group, and R 2 to R 4 Surface-modified hollow aluminosilicate particles (F-11) were prepared in the same manner as in Preparation Example 2-1, except that a compound (E-2) represented by Chemical Formula 1, which is a methoxy group, was used.

[0349] Preparation Example 2-12: Preparation of surface-modified hollow aluminosilicate particles (F-12)

[0350] The above R 1 is a methyl group, and R 2 to R 4 Surface-modified hollow aluminosilicate particles (F-12) were prepared in the same manner as in Preparation Example 2-1, except that the non-reactive resin (E-8) of Synthesis Example 4 was used instead of the compound (E-1) represented by Chemical Formula 1, which is a methoxy group.

[0352] Preparation Example 2-13: Preparation of surface-modified hollow aluminosilicate particles (F-13)

[0353] The above R 1 is a methyl group, and R 2 to R 4Surface-modified hollow aluminosilicate particles (F-13) were prepared in the same manner as in Preparation Example 2-1, except that the non-reactive resin (E-9) of Synthesis Example 5 was used instead of the compound (E-1) represented by Chemical Formula 1, which is a methoxy group.

[0355] Examples and Comparative Examples: Preparation of Resin Composition for Anti-reflective Films

[0356] A resin composition for an anti-reflective film was prepared by mixing each component according to the compositions of Tables 1 and 2 below (weight%).

[0358] Example 1 Example 2 Example 3 Example 4 Example 5 Example 6 Example 7 Example 8 Example 9 Example 10 Example 11 Example 12 Surface-modified hollow aluminosilicate particles (F) F-1 2                 4 2 2 F-2   2                   F-3     2                 F-4                       F-5                       F-6                       F-7                       F-8       2   2         F-9         2   2         F-10                       F-11                       F-12               2       F-13                 2     Amorphous silica particles (B) B-1 2 2 2 2 2     2 2 2 2 B-2           2 2         B-3                       Binder resin (C) C-1 0.5 0.5 0.5 0.5 0.5 0.5 0.5 0.5 0.5 0.5 0.5 0.5 Solvent (D) D-1 76.4 76.4 76.4 76.4 76.4 76.4 76.4 76.4 76.4 76.4 47.8 76.4 D-2 19.1 D-3 19.1 19.1 19.1 19.1 19.1 19.1 19.1 19.1 19.1 19.1 47.8 D-4 D-5

[0360] Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 Comparative Example 6 Comparative Example 7 Comparative Example 8 Comparative Example 9 Comparative Example 10 Comparative Example 11 Comparative Example 12 Surface-modified hollow aluminosilicate particles (F) F-1               2 2 2 2 2 F-2                     F-3                     F-4 2                   F-5   2                 F-6     2               F-7       2             F-8             2       F-9                   F-10         2           F-11           2         F-12                     F-13                     Amorphous silica particles (B) B-1 2 2 2 2 2 2     2 2 2 2 B-2                     B-3             2 2     Binder resin (C) C-1 0.5 0.5 0.5 0.5 0.5 0.5 0.5 0.5 0.5  0.5  0.5  0.5  Solvent (D) D-1 76.4 76.4 76.4 76.4 76.4 76.4 76.4 76.4 95.5 28.7 76.4 76.4 D-2 D-3 19.1 19.1 19.1 19.1 19.1 19.1 19.1 19.1 66.8 D-4 19.1 D-5 19.1

[0362] F-1 to F-13: Surface-modified hollow aluminosilicate particles of Preparation Examples 2-1 to 2-13

[0363] B-1: PM-09 (average particle size 22 nm, Tokuyama Co.)

[0364] B-2: X-20 (average particle size 12 nm, Tokuyama Co.)

[0365] B-3: QSG-100 (average particle size 110 nm, Shin-Etsu Chemical)

[0366] C-1: Silicone resin (KR-220L, Shin-Etsu)

[0367] D-1: Propylene glycol monomethyl ether acetate

[0368] D-2: Ethanol

[0369] D-3: 1-Butanol

[0370] D-4: Cyclohexanol

[0371] D-5: Propylene glycol diacetate

[0373] Experimental Example:

[0374] Anti-reflective films were prepared as follows using the resin compositions for anti-reflective films prepared in the above examples and comparative examples, and the physical properties of the anti-reflective films were evaluated by the following method, and the results are shown in Tables 3 and 4 below.

[0375] In addition, the a / b values ​​were calculated and shown in Tables 3 and 4. Here, a is the average particle size of hollow aluminosilicate particles, and b is the average particle size of amorphous silica particles.

[0377] Anti-reflective film manufacturing

[0378] The resin compositions for anti-reflective films prepared in the above examples and comparative examples were each spin-coated onto a 4-inch silicon wafer (manufactured by SK Siltron), and then pre-baked at 100°C for 60 seconds using a hot plate. After cooling the pre-baked substrate to room temperature, it was post-baked in an oven at 200°C for 300 seconds. The thickness of the cured film was 100 nm.

[0380] (1) Refractive index measurement

[0381] For the above-described cured film substrate, linear polarization was measured in the wavelength range of 200 nm to 1000 nm using an ellipsometer M-2000 (manufactured by JA Woollam Co.) under conditions of 25° and 50%RH with incident angles of 65, 70, and 75°. The measured linear polarization data (Ellipsometry data(Ψ, Δ)) was fitted using Complete EASE software with the Cauchy model of Equation 2 below so that the MSE was 20 or less, and the refractive index at a wavelength of 550 nm was calculated.

[0382] [Mathematical Formula 2]

[0383]

[0385] In the above mathematical formula 2, n(λ) is the refractive index at wavelength λ, λ is in the range of 300 nm to 1800 nm, and A, B, and C are Cauchy parameters.

[0387] (2) Crack resistance

[0388] A cured film substrate was manufactured in the same manner as the above manufacturing method, except that the thickness of the cured film was formed to be 500 nm.

[0389] The surface of the above-mentioned cured film substrate was observed to check for the occurrence of cracks, and crack resistance was evaluated according to the following evaluation criteria.

[0390] <Evaluation Criteria>

[0391] ○: No cracks occurred

[0392] ×: Crack occurred

[0394] (3) Flatness of the coating

[0395] For the above-mentioned cured film substrate, the Ra value was measured using an atomic force microscope (AFM) Nanoscope (Bluecar AXS), and the flatness of the film was evaluated according to the following evaluation criteria.

[0396] <Evaluation Criteria>

[0397] ◎: Ra value less than 6nm

[0398] ○: Ra value 6nm or higher and less than 9nm

[0399] ×: Ra value 9nm or higher

[0401] (4) Moisture permeability in high temperature and high humidity

[0402] For the above-mentioned cured film substrate, the refractive index was measured before and after 500 hours of storage in a constant temperature and humidity chamber PR-1J (ESPEC) at a temperature of 85℃ and a humidity of 85%, and the change in refractive index was calculated using the following mathematical formula 3 to evaluate the moisture permeability at high temperature and high humidity according to the following evaluation criteria.

[0403] [Mathematical Formula 3]

[0404] Change in refractive index = [(Refractive index after storage - Refractive index before storage) / Refractive index before storage] × 100

[0405] <Evaluation Criteria>

[0406] ◎: Less than 1%

[0407] ○: 1% or more and less than 5%

[0408] ×: 5% or more

[0410] (5) Water permeability of the developer and stripper solution

[0411] For the above-mentioned cured film substrate, the refractive index was measured before and after 5 minutes of immersion in 2.38% tetramethylammonium hydroxide (TMAH) (developer) and methylpyrrolidone (stripping solution), respectively, and the change in refractive index was calculated using the following Equation 4 to evaluate the developer and stripping solution according to the following evaluation criteria. Moisture permeability was evaluated.

[0412] [Mathematical Formula 4]

[0413] Change in refractive index = [(Refractive index after immersion - Refractive index before immersion) / Refractive index before immersion] × 100

[0414] <Evaluation Criteria>

[0415] ◎: Less than 1%

[0416] ○: 1% or more and less than 5%

[0417] ×: 5% or more

[0419] (6) Level of foreign matter

[0420] Contamination was measured on the above-manufactured cured film substrate using KEYENCE (VHX-S770E). The number of foreign substances was measured, and the level of foreign substances was evaluated according to the following evaluation criteria.

[0421] <Evaluation Criteria>

[0422] ◎: Less than 50

[0423] ○: 50 or more, less than 100

[0424] ×: 100 or more

[0426] (7) Long-term stability

[0427] A cured film was obtained by performing the same method as the anti-reflective film manufacturing method before and after storing (leaving) the resin composition for the anti-reflective film prepared in the above examples and comparative examples at 40°C for 2 weeks.

[0428] The number of foreign substances was measured by measuring contamination on the hardened film obtained before and after storage using KEYENCE (VHX-S770E).

[0429] The change in the level of foreign matter over time was calculated using the following mathematical formula 5, and the level of foreign matter over time was evaluated according to the following evaluation criteria.

[0430] [Mathematical Formula 5]

[0431] Change in foreign matter over time = [(Number of foreign matter after storage - Number of foreign matter before storage) / Number of foreign matter before storage] × 100

[0433] <Evaluation Criteria>

[0434] ◎: Less than 10%

[0435] ○: 10% or more and less than 30%

[0436] △: 30% or more and less than 70%

[0437] ×: 70% or more

[0439] Example 1 Example 2 Example 3 Example 4 Example 5 Example 6 Example 7 Example 8 Example 9 Example 10 Example 11 Example 12 Average particle size (nm) of hollow aluminosilicate particles 78 78 78 40 150 40 150 78 78 78 78 78 Average particle size (nm) of amorphous silica particles 22 22 22 22 22 12 12 22 22 - 22 22 Si / Al ratio 12 12 12 10 8 10 8 12 12 12 12 12 a / b value 3.5 3.5 3.5 1.8 6.8 3.3 12.5 3.5 3.5 - 3.5 3.5 Refractive index 1.24 1.25 1.25 1.27 1.22 1.26 1.21 1.25 1.25 1.20 1.24 1.25 Crack resistance ○ ○ ○ ○ ○ ○ ○ ○ ○ ○ ○ ○ flatness ◎ ◎ ◎ ◎ ○ ◎ ○ ◎ ◎ ○ ◎ ◎ High temperature and high humidity moisture permeability ◎ ◎ ○ ◎ ○ ◎ ○ ◎ ◎ ◎ ○ ○ Developer vapor permeability ◎ ◎ ○ ○ ○ ○ ○ ◎ ○ ◎ ○ ○ Release solution moisture permeability ◎ ◎ ○ ○ ○ ○ ○ ◎ ○ ◎ ○ ○ Foreign matter level ◎ ◎ ◎ ◎ ○ ◎ ○ ◎ ◎ ◎ ◎ ◎ Long-term stability ◎ ◎ ◎ ◎ ◎ ◎ ◎ ◎ ◎ ◎ ○ ○

[0441] Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 Comparative Example 6 Comparative Example 7 Comparative Example 8 Comparative Example 9 Comparative Example 10 Comparative Example 11 Comparative Example 12 Average particle size (nm) of hollow aluminosilicate particles 78 78 78 78 74 74 40 78 78 78 78 78 Average particle size (nm) of amorphous silica particles 22 22 22 22 22 22 110 110 22 22 22 22 Si / Al ratio 12 12 12 12 16 5 10 12 12 12 12 12 a / b value 3.5 3.5 3.5 3.5 3.4 3.4 0.4 0.7 3.5 3.5 3.5 3.5 Refractive index 1.28 1.31 1.33 1.35 1.38 1.41 1.41 1.39 1.24 1.24 1.24 1.24 Crack resistance ○ ○ ○ ○ X X X X ○ ○ ○ ○ flatness ○ ○ ○ ○ X X X X ◎ ◎ ◎ ◎ High temperature and high humidity moisture permeability X X X X X X ○ ○ ◎ ◎ ◎ ◎ Developer vapor permeability X X X X X X ○ ○ ◎ ◎ ◎ ◎ Release solution moisture permeability X X X X X X ○ ○ ◎ ◎ ◎ ◎ Foreign matter level X X X X X X ○ ○ ○ ○ X X Long-term stability △ △ △ △ △ △ ○ ○ X X X X

[0443] As shown in Tables 3 and 4 above, according to the present invention, the resin compositions for anti-reflective films of Examples 1 to 12, which include hollow aluminosilicate particles whose surface is modified with a compound represented by Formula 1 or a non-reactive resin and have a Si / Al molar ratio of 7 to 15, and an alcohol compound as a solvent in an amount of 5 to 50 weight% relative to 100 weight% of the total solvent, were confirmed to exhibit a low refractive index, suppress crack formation during film formation, have excellent flatness of the film, prevent particle aggregation and foreign matter generation, prevent moisture adsorption under high temperature and high humidity, and prevent moisture penetration by the developer and stripper, as well as excellent stability over time.

[0444] On the other hand, the resin compositions for anti-reflective films of Comparative Examples 1 to 12 were found to have an increased refractive index, poor crack resistance and / or flatness of the film, the occurrence of foreign matter, moisture permeability under high temperature and high humidity, moisture permeability caused by the developer and stripper solution, or reduced stability over time.

[0446] As specific parts of the present invention have been described in detail above, it is evident to those skilled in the art that such specific descriptions are merely preferred embodiments and do not limit the scope of the present invention. Those skilled in the art will be able to make various applications and modifications within the scope of the present invention based on the above description.

[0447] Accordingly, the substantial scope of the present invention shall be defined by the appended claims and their equivalents.

Claims

Claim 1 A resin composition for an anti-reflective film comprising hollow aluminosilicate particles, a binder resin, and a solvent, wherein the hollow aluminosilicate particles have a Si / Al molar ratio of 7 to 15 and their surface is modified with a compound represented by the following Chemical Formula 1 or a non-reactive resin, and the solvent comprises an alcohol compound in an amount of 5 to 50 weight% based on 100 weight% of the total solvent: [Chemical Formula 1] In the above equation, R 1 C1-C 20 It is an alkyl group of, and R 2 to R 4 Each is independently a C1-C4 alkoxy group. Claim 2 A resin composition for an anti-reflective film according to claim 1, wherein the average particle size of the hollow aluminosilicate particles is 30 to 150 nm. Claim 3 In claim 1, the non-reactive resin is a resin composition for an anti-reflective film comprising a repeating unit represented by the following chemical formula 2: [Chemical Formula 2] In the above equation, R 5 is a hydrogen atom or a methyl group, and L 1 is non-existent or C1-C 10 The alkylene group or C1-C 10 It is an oxyalkylene group of, and R 6 is a hydroxyl group, a C1-C4 alkoxy group, or a halogen, and R 7 Silver is a hydrogen atom or C1-C 20 It is an alkyl group, and n is an integer from 1 to 3. Claim 4 In claim 1, the alcohol compound is C1-C 10 A resin composition for an anti-reflective film that is a monoalcohol compound. Claim 5 A resin composition for an anti-reflective film according to claim 1, wherein the alcohol compound is one or more selected from the group consisting of methanol, ethanol, isopropyl alcohol, butanol, pentanol, hexanol, and 3-methoxy-1-butanol. Claim 6 A resin composition for an anti-reflective film according to claim 1, further comprising amorphous silica particles. Claim 7 In claim 6, a resin composition for an anti-reflective film satisfying the following mathematical formula 1: [Mathematical Formula 1] 1 ≤ a / b ≤ 15 In the above formula, a is the average particle size of hollow aluminosilicate particles, and b is the average particle size of amorphous silica particles. Claim 8 In claim 1, the cured film formed from the resin composition for an anti-reflective film is a resin composition for an anti-reflective film having a refractive index of 1.20 to 1.35 at 550 nm. Claim 9 An anti-reflective film formed using a resin composition for an anti-reflective film according to any one of claims 1 to 8. Claim 10 A solid-state imaging element having an anti-reflective film according to claim 9.